Laser-treatment-induced surface integrity modifications of stainless steel - Na Gong; Yuefan Wei; Tzee Luai Meng; Rahul Karyappa; Jing Cao; Chee Kiang Ivan Tan; Ady Suwardi; Qiang Zhu; Hongfei Liu (Materials Research Express, 2023)
Scanning of a high-power laser beam on the surface of martensitic stainless steel (SS420) has been studied, addressing the effect of scanning rate V on integrity modifications in the near-surface regions. Structural, compositional, and crystallographic characterizations revealed the presence of ablations, surface melting/resolidification, surface oxidations, and austenite ( γ -phase) precipitations when V ≤ 20 mm s ^−1 . Melt pool (MP), heat affected zone (HAZ), and base material have been clearly distinguished at the cross-section of the slow-scanned samples. Adjacent MPs partially overlapped when V = 5 mm s ^−1 . The γ -phase precipitations solely occurred in the MPs, i.e., of ∼ 400 μ m deep for V = 5 mm s ^−1 , while oxidations dominantly occurred in the surface regions of shallower than ∼30 μ m within the MPs. Compositional analysis revealed increased Cr-, Mn-, and Si-to-Fe ratios at the laser-scanned surface but without variations along the surface normal direction. The enhanced surface hardness has been achieved up to 805 HV, and the hardness monotonically decreased when moving deeper (i.e., ∼1000 μ m) into the base material. These observations shed new light on surface engineering of metallic alloys via laser-based direct energy treatments.